(Retracted) The Development of Learning Resources to Avoid Violence Acts on Children - Gunadi, Andi Ahmad (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
Violence in children is a physical act of aggression by parents who can cause trauma and even bring death to children. Purpose of research: 1. knowing the appropriate role of  parenting; 2. knowing the acts of violence on children; 3. knowing the source of learning to avoid acts of violence on children. Research method used qualitative description, data collection: observation and interview in the form of discussion. The result of research: Parenting role consists of authoritarian, democratic, authoritative, and permissive. Violence occurs in children in the form of physical, psychological, and economic violence. Learning resources that can be utilized in an effort to avoid acts of violence in children can be made based on material elements or messages, people, and materials.